Dendrogram Analysis of Large-Area CARMA Images in Perseus: the Dense Gas in NGC 1333, Barnard 1, and L1451 - Storm, Shaye (2014)
We present spectral line maps of the dense gas across 400 square arcminutes of the Perseus Molecular Cloud, focused on NGC 1333, Barnard 1, and L1451. We constructed these maps as part of the CARMA Large Area Star-formation Survey (CLASSy), which is a CARMA key project that connects star forming cores to their natal cloud environment. This is achieved by leveraging CARMA's high angular resolution, imaging capability, and high efficiency at mosaicing large areas of the sky. CLASSy maps capture the structure and kinematics of N2H+, HCN, and HCO+ J=1-0 emission from thousand AU to parsec scales in three evolutionarily distinct regions of Perseus (in addition to two regions in Serpens). We show results from a non-binary dendrogram analysis of the Perseus N2H+ emission, which answers questions about the turbulent properties of the dense gas across evolutionary stages and across the range of size scales probed by CLASSy. There is a flat relation between mean internal turbulence and structure size for the dense gas in NGC 1333 and Barnard 1, but the magnitude of internal turbulence increases with nearby protostellar activity; the dense gas in the B1 main core and NGC 1333, which have active young stars, are characterized by mostly transonic to supersonic turbulence, while the filaments and clumps southwest of the B1 main core, which have no active young stars, have mostly subsonic turbulence. We have recently completed the observations of L1451, and results for that region will be revealed at the meeting. Released CLASSy data products can be found on our project website.